2020
DOI: 10.5194/bg-17-1717-2020
|View full text |Cite
|
Sign up to set email alerts
|

Warming enhances carbon dioxide and methane fluxes from Red Sea seagrass (<i>Halophila stipulacea</i>) sediments

Abstract: Abstract. Seagrass meadows are autotrophic ecosystems acting as carbon sinks, but they have also been shown to be sources of carbon dioxide (CO2) and methane (CH4). Seagrasses can be negatively affected by increasing seawater temperatures, but the effects of warming on CO2 and CH4 fluxes in seagrass meadows have not yet been reported. Here, we examine the effect of two disturbances on air–seawater fluxes of CO2 and CH4 in Red Sea Halophila stipulacea communities compared to adjacent unvegetated sediments using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
0
11
2
Order By: Relevance
“…An unprecedented heatwave in 2010-2011 led to a 22% loss of seagrass cover in Shark Bay, Australia, resulting in an estimated increase in national CO 2 emissions from land-use change by 4-21% per annum 93 . Experimentally increasing the temperature up to 37 °C led to a fourfold increase in methane fluxes if compared with the community held at 25 °C from Red Sea seagrass sediments 143 . Temperature increase is likely to lead to a range of different responses in BCEs, including an increase or decrease in primary productivity, faster decomposition of organic matter and changes in BCE spatial distribution, but there are still many uncertainties regarding the nature and extent of these changes and how they might differ with latitude and environmental setting 108,118 .…”
Section: Relevance To Nationally Determined Contributionsmentioning
confidence: 93%
See 1 more Smart Citation
“…An unprecedented heatwave in 2010-2011 led to a 22% loss of seagrass cover in Shark Bay, Australia, resulting in an estimated increase in national CO 2 emissions from land-use change by 4-21% per annum 93 . Experimentally increasing the temperature up to 37 °C led to a fourfold increase in methane fluxes if compared with the community held at 25 °C from Red Sea seagrass sediments 143 . Temperature increase is likely to lead to a range of different responses in BCEs, including an increase or decrease in primary productivity, faster decomposition of organic matter and changes in BCE spatial distribution, but there are still many uncertainties regarding the nature and extent of these changes and how they might differ with latitude and environmental setting 108,118 .…”
Section: Relevance To Nationally Determined Contributionsmentioning
confidence: 93%
“…Positive steps can be taken to mitigate sea-level rise through restoration projects that include a mix of species and at increased densities and scale, while taking into account local hydrology, the potential for landward 0123456789();: expansion of mangroves and tidal marshes, and relevance to the socio-economic factors affecting the local communities 109,111,141,142 . Anthropogenic warming can also have an impact; for example, increasing temperatures can result in changing gas fluxes in BCEs that lead to enhanced emissions 93,118,143 . The effect of temperature increase on greenhouse gas emissions in seagrass meadows has indicated the potential negative effects of climate change.…”
Section: Relevance To Nationally Determined Contributionsmentioning
confidence: 99%
“…How seagrass systems might contribute to these emissions has received comparably little attention, although valuable studies have been published (Bahlmann et al, ; Barber & Carlson, ; Deborde et al, ; Garcias‐Bonet & Duarte, ; Oremland, ). Temperature increases have been shown to enhance methane emissions from freshwater systems (Yvon‐Durocher, Hulatt, Woodward, & Trimmer, ; Yvon‐Durocher, Montoya, Woodward, Jones, & Trimmer, ), and recently, it has been shown that methane emission from seagrass meadows rises substantially when seagrasses are disturbed (Burkholz, Garcias‐Bonet, & Duarte, ; Lyimo et al, ), and based on calculations of methane emission in seagrass sediments from the Red Sea, it has been suggested that the present estimations of methane emissions from natural systems might have to be increased by about 30% to account for hitherto unrecognized contributions from seagrass systems (Garcias‐Bonet & Duarte, ). In general, the methane production of biological systems is closely correlated with the productivity of the plants within the system (Borges, Speeckaert, Champenois, Scranton, & Gypens, ; Bridgham et al, ), and for wetlands in particular, there is a clear positive correlation between emission of methane and net ecosystem production (Whiting & Chanton, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is substantially lower than what has been observed in other marine habitats; for example, saltmarshes can emit over 10,000 µg m −2 h −1 (Whiting and Chanton, 1993). However, stressors (such as light reduction, habitat fragmentation, and warming) can dramatically increase CH 4 emission in seagrass systems (Lyimo et al, 2018;Burkholz et al, 2020;George et al, 2020). Vegetation loss or alteration in macrophyte species composition may also stimulate methanogenesis in the sediment (Sutton-Grier and Megonigal, 2011;Lyimo et al, 2018;Al-Haj and Fulweiler, 2020).…”
Section: Introductionmentioning
confidence: 91%